2017
DOI: 10.1016/j.crci.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Cu- and Zn-complex-catalyzed methanolysis of the chemical warfare nerve agents soman, sarin, and VX

Abstract: Full paper/M emoireThe Cu-and Zn-complex-catalyzed methanolysis of the chemical warfare nerve agents soman, sarin, and VXLes complexes de Cu et Zn catalysent la m ethanolyse des agents neurotoxiques de guerre chimique soman, sarin et VX

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In contrast, nanosized particles (NPs) have been reported as promising prospective reactive sorbent materials [7,11,22] which have the ability to potentiate the neutralization of CWAs [23,24]. In comparison with the conventional materials, nanostructures have attracted great interest due to their enhanced reactivity towards CWAs, owing to large specific surface and reactive edges, corner defects and unusual lattice planes [22]. Prasad et al reported the decontamination of sulfur mustard (HD) and its surrogate, 2-chloroethyl ethyl sulfide (CEES) by manganese oxide nanosheets and nanotubes and also by titania nanotubes [11,22,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, nanosized particles (NPs) have been reported as promising prospective reactive sorbent materials [7,11,22] which have the ability to potentiate the neutralization of CWAs [23,24]. In comparison with the conventional materials, nanostructures have attracted great interest due to their enhanced reactivity towards CWAs, owing to large specific surface and reactive edges, corner defects and unusual lattice planes [22]. Prasad et al reported the decontamination of sulfur mustard (HD) and its surrogate, 2-chloroethyl ethyl sulfide (CEES) by manganese oxide nanosheets and nanotubes and also by titania nanotubes [11,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the conventional materials, nanostructures have attracted great interest due to their enhanced reactivity towards CWAs, owing to large specific surface and reactive edges, corner defects and unusual lattice planes [22]. Prasad et al reported the decontamination of sulfur mustard (HD) and its surrogate, 2-chloroethyl ethyl sulfide (CEES) by manganese oxide nanosheets and nanotubes and also by titania nanotubes [11,22,25]. CWAs underwent degradation on the surface of these nanostructures through hydrolysis reactions [4,11,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation